DAIDZEIN: A REVIEW OF PHARMACOLOGICAL EFFECTS - Sun, Meng-Yao; Ye, Ying; Xiao, Ling; Rahman, Khalid; Xiad, Wei; Zhang, Hong (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Daidzein is an isoflavone with extensive nutritious value and is mainly extracted from soy plants. It is also calledphytoestrogen due to its structural similarity to the human hormone estrogen. However, daidzein is distinct from estrogen due to thespecificity of the estrogen receptor (ER) complex. In recent years, the pharmacological properties of daidzein have been extensivelyinvestigated and considerable progress has been made. The present review aims to evaluate the pharmacological effects andmechanisms of daidzein as reported in scientific literature.Materials and Methods: Studies were identified as reported in PubMed, Elsevier, Scholar, and Springer over the last ten years andthis resulted in the identification of 112 papers.Results: Daidzein is reported to play a significant role in the prevention and treatment of a variety of diseases such as cancer,cardiovascular disease, diabetes, osteoporosis, skin disease, and neurodegenerative disease. This pharmacological activity isattributed to various metabolites including equol and trihydroxy isoflavone.Conclusion: Daidzein appears to play a significant role in the prevention of a variety of diseases and has the potential of being usedin a clinical setting. However, further research is needed to understand its molecular mechanisms and safety for use in humans.